2010
DOI: 10.1002/cncr.25425
|View full text |Cite
|
Sign up to set email alerts
|

First‐line chemotherapy with capecitabine and temozolomide in patients with metastatic pancreatic endocrine carcinomas

Abstract: BACKGROUND Temozolomide is an active agent in metastatic pancreatic endocrine carcinomas. In vitro data indicate that the combination of capecitabine and temozolomide is synergistic for induction of apoptosis in neuroendocrine tumor cell lines. The authors retrospectively evaluated the efficacy of capecitabine and temozolomide in 30 patients with metastatic pancreatic endocrine carcinomas to assess response rate, progression free survival (PFS), and overall survival (OS). METHODS Patients with metastatic, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
408
1
19

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 668 publications
(448 citation statements)
references
References 41 publications
(51 reference statements)
13
408
1
19
Order By: Relevance
“…Temozolomide (Table 3) [22][23][24][25][26][27][28][29] Temozolomide is an oral alkylating agent that is used to treat glioblastoma and melanoma. Because the side-effects of temozolomide are mild and it is an oral drug, temozolomide chemotherapy is expected to be less stressful for patients, and several studies of combination therapies with other drugs have been conducted in addition to a study of temozolomide alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temozolomide (Table 3) [22][23][24][25][26][27][28][29] Temozolomide is an oral alkylating agent that is used to treat glioblastoma and melanoma. Because the side-effects of temozolomide are mild and it is an oral drug, temozolomide chemotherapy is expected to be less stressful for patients, and several studies of combination therapies with other drugs have been conducted in addition to a study of temozolomide alone.…”
Section: Introductionmentioning
confidence: 99%
“…When used as a monotherapy, the response rate was 14%, the median PFS was 7 months, and the median survival time was 16 months [23]. While the results of temozolomide monotherapy were marginal, all the studies that have been conducted examining combination therapy with capecitabine have reported promising results with regard to the response rate, PFS, and survival time, and this combination, in particular, has attracted interest [24][25][26][27][28][29]. The Eastern Cooperative Oncology Group (ECOG) is currently conducting a NA not available, PFS progression-free survival Alkylating agents, including temozolomide, induce the methylation of the O 6 -position of guanine, which results in DNA mismatching and ultimately results in apoptosis and tumor cell death.…”
Section: Introductionmentioning
confidence: 99%
“…The initial experiences with temozolamide and capacetabine, in the setting of metastatic pNETs disease, show a radiographic response rate of approximately 60 %, with an estimated median progression-free survival of 14 months, and median overall survival of 83 months [87][88][89]. Another advantage of this synergistic regimen is its favorable toxicity profile compared to streptomycin [87].…”
Section: Cytoreductive Chemotherapymentioning
confidence: 99%
“…Nonspecific chemotherapeutic regimes including streptozotocin in combination with 5-fluorouracil (FU) or temozolomide in combination with capecitabine have yielded promising results in a "select" subgroup of pancreatic NETs [20,21]. For grade 3 neuroendocrine cancers, even fewer treatment options are available, and conventional archaic cytotoxic chemotherapy schemes are usually applied [5,22].…”
Section: Introductionmentioning
confidence: 99%